Development of a Two-Channel Simultaneous Photoplethysmography Recording System - Kim Soon Chong; Kok Beng Gan; Mohd. Ali Mohd. Alauddin (LPPM ITB, 2012)
Multi-site photoplethysmograph (PPG) recording enables researchers to study the vascular and hemodynamic properties of human subjects. Currently, there is no commercial system available in the market to perform either one channel or multi-channel PPG recording. PPG is an optoelectronic technique that measures changes in blood volume associated with cardiac contraction. The measurements can be obtained from fingertips, ear lobes and toes due to their low absorption and high degree of vasculature. The main objective of this project is to develop a two-channel simultaneous PPG recording system to acquire PPG signals from two different physiological sites using a Nellcor equivalent PPG probe. MATLAB software was used during the development phase to ensure rapid prototyping. The experiment results show that there was no inter -channel delay in the developed two-channel PPG system. Our preliminary results show that the delays between the left and the right arm were from 4 to 12 ms in three healthy random subjects. The system is portable, powered by universal serial bus (USB) and allows the user to do the PPG data acquisition in a clinical setting.